Radio-echo soundings on Icelandic temperate glaciers: history of techniques and findings. Issue 81 (11th April 2020) - Björnsson, Helgi; Pálsson, Finnur
Abstract: Since the mid-1970s radio-echo soundings have been conducted on Iceland's temperate glaciers. Since then, low-frequency radar technology has furthered the study of most of the island's ice caps. Their masses and volumes have been quantified and detailed subglacial topographic maps produced which demarcate glacial drainage basins and identify subglacial lakes and volcanoes. Even internal tephra layers have been charted. The resulting data have been used to force and validate models of past and future glacier evolution. Many practical applications in glacier hydrology have come into being, including hydropower management, road and bridge planning and the prediction of catastrophic flood paths from subglacial eruption sites. Finally, emerging landscapes can now be foreseen in places where glaciers may soon disappear. These achievements would not have been possible without the advances in RES technology.